Efektivitas Campuran Karbon Kulit Umbi Talas (Colocasia esculenta) dan Bleaching Earth untuk Penjernihan Minyak Jelantah - Popy Meylani; Umar Kalmar Nizar (MASALIQ, 2026)
Purification of used cooking oil is necessary to reduce the content of impurity compounds formed during repeated use so that the physicochemical quality of the oil can be improved. This study aimed to evaluate the effectiveness of a mixture of taro corm peel carbon (Colocasia esculenta) and bleaching earth as an adsorbent in the purification of used cooking oil. The carbon was prepared by carbonizing taro corm peel at 250 °C for 1 hour and was then combined with bleaching earth in five adsorbent compositions, namely K100, K75BE25, K50BE50, K25BE75, and BE100. The adsorption process was conducted using 5 g of adsorbent in 100 mL of used cooking oil with stirring at 200 rpm for 60 minutes at room temperature. The carbon characteristics were analyzed based on moisture content, ash content, and fixed carbon content, whereas the quality of the purified oil was evaluated based on acid value, saponification value, density, and flow rate. The characterization results showed that taro corm peel carbon had a moisture content of 2.93%, an ash content of 8.49%, and a fixed carbon content of 88.58%. Variations in adsorbent composition affected the quality of used cooking oil after purification, with the K50BE50 treatment demonstrating the best performance based on the lowest acid value and better saponification value, density, and flow rate than the other treatments. These findings indicate that a balanced composition of taro corm peel carbon and bleaching earth produced the most effective adsorption process. The combination of these two adsorbents has the potential to be developed as an effective, economical, and environmentally friendly biomass-based alternative adsorbent for improving the quality of used cooking oil.